A case of membranous glomerulonephritis presenting as pulmonary embolism and acute hyperlipidaemia - Hartland, A J (Copyright 2002 Journal of Clinical Pathology, 2002)
This paper describes the case of a 48 year old man who presented with acute hyperlipidaemia following pulmonary embolism. Subsequent investigation revealed that the hyperlipidaemia was secondary to nephrotic syndrome of glomerulonephritis. The case illustrates the importance of investigating acute hyperlipidaemia for its underlying causes.